Metabolic Cost of the Immune Response During Early Ontogeny of the Scallop Argopecten purpuratus - Rojas, Isis; Rivera-Ingraham, Georgina A.; Cárcamo, Claudia B.; Jeno, Katherine; de la Fuente-Ortega, Erwin; Schmitt, Paulina; Brokordt, Katherina (Frontiers in Physiology, 2021)
The scallop Argopecten purpuratus is an important resource for Chilean and Peruvian aquaculture. Seed availability from commercial hatcheries is critical due to recurrent massive mortalities associated with bacterial infections, especially during the veliger larval stage. The immune response plays a crucial role in counteracting the effects of such infections, but being energetically costly, it potentially competes with the physiological and morphological changes occurring during early development, which are equally expensive. Consequently, in this study, energy metabolism parameters at the individual and cellular levels, under routine-basal status and after the exposure to the pathogenic strain bacteria (Vibrio splendidus VPAP18), were evaluated during early ontogeny (trochophore, D-veliger, veliger, pediveliger, and early juveniles) of A. purpuratus. The parameters measured were: (1) metabolic demand, determined as oxygen consumption rate; and (2) ATP supplying capacity, measured by key mitochondrial enzymes activities [citrate synthase (CS), electron transport system (ETS), and ETS/CS ratio, indicative of ATP supplying efficiency], mitochondrial membrane potential (ΔΨm), and mitochondrial density (ρm), using in-vivo image analysis. Data revealed that metabolic demand/capacity vary significantly throughout early development, with trochophores being the most efficient in terms of energy supplying capacity under basal conditions. ATP supplying efficiency decreased linearly with larval development, attaining its lowest level at the pediveliger stage, and increasing markedly in early juveniles. Veliger larvae at basal conditions were inefficient in terms of energy production vs. energy demand (with low ρm, ΔΨm, enzyme activities, and ETS:CS). Post-challenged results suggest that both trochophore and D-veliger would have the necessary energy to support the immune response. However, due to an immature immune system, the immunity of these stages would rely mainly on molecules of parental origin, as suggested by previous studies. On the other hand, post-challenged veliger maintained their metabolic demand but decreased their ATP supplying capacity, while pediveliger increased CS activity. Overall, results suggest that veliger larvae exhibit the lowest metabolic capacity to overcome a bacterial challenge, coinciding with previous works showing a reduced capacity to express immune-related genes. This would result in a higher susceptibility to pathogen infection, potentially explaining the higher mortality rates occurring during A. purpuratus farming.